The Moderating Role of Generation in the Relationship Between Remote Working and Employee Performance - Abou Abdallah, Murielle (2022)
The relationship between remote working and employee performance has been explored by various previous studies. However, the outcomes of these studies have been contradictory. While some studies have found that remote working has no association with employee performance, others have established that remote working and employee performance are either positively or negatively associated with employee performance. This inconsistency in the outcome of prior studies, attracted our interest to test whether or not, remote working and employee performance are associated. Additionally, we were interested to understand whether or not, age (described in form of generations) has a moderating role in the relationship between employee performance and remote working. To realize our objectives, this study employed role-based measurement of employee performance which introduces five roles that an employee can undertake in a company or organization, and these include job holder, career seeker, innovator, team member, and organization member. By incorporating social exchange theory with lifespan theories particularly focusing on future perspectives, we suggest that age has a moderating impact on the relationship between remote working and employee performance such that younger generations employees are positively associated with remote work and have high job performance while working remotely, and older generation employees are negatively associated with remote working such that they have low job performance while working remotely. Using data gathered from 285 respondents in Lebanon (who are employees working in diverse industries and organizations) and analyzed using multiple regression analysis. The analysis outcome shows that remote working positively associate with employee performance in all the roles that an employee can hold. However, the analysis also revealed that age (or generation) does not have a moderating role in the relationship between remote working and employee performance, but age associates with remote working such that younger generations positively associate with remote working while older generation employees negatively associate with remote working. The association between age and remote working concerns predilection to remote working and not performance. The outcome of this study suggests that, in deploying roles and tasks to employees especially in a remote working arrangement, managers should take great consideration that employees in regard to their generations or age are different, special, and unique in their own ways as well as in different roles.